Significant motor improvement in an infant with congenital heart disease and a rolandic stroke: The impact of early intervention. (3rd April 2017) - Gallagher, Anne; Dagenais, Lynn; Doussau, Amélie; Décarie, Jean-Claude; Materassi, Manuela; Gagnon, Karine; Prud'homme, Joelle; Vobecky, Suzanne; Poirier, Nancy; Carmant, Lionel
ABSTRACT: Objective : To report the impact of early motor intervention in an infant with congenital heart disease (CHD) and a stroke. Methods and Results : A 35-week newborn with a complex CHD and a normal MRI presented with early motor developmental delay at 2 months. She began an intervention program, which included biweekly motor developmental therapy with a physiotherapist, parental education, and daily home exercises. At 4 months, she underwent cardiac surgery. Following surgery, she was diagnosed with a stroke involving the right sylvian artery territory. She continued her intensive intervention program. The 12-month assessment revealed an evident gain of motor function. Despite MRI evidence of a chronic infarct involving the primary motor cortex, the child had normal motor functions. Conclusion : This case report supports the positive impact of early intervention in infants with CHD and its potential effect on enhancing neuroplasticity, even in children with cerebro-vascular accidents involving areas of motor function.